Effects of drought stress and plant growth-promoting rhizobacteria on sudden-death disease (Cytospora euginae) development of clove. Issue 1 (January 2022) - Budi, F S; Widodo,
Abstract: Recently, a sudden-death disease caused by Cytospora euginae has been reported in several major clove-producing areas in Indonesia. Previous surveys indicated that drought stress factors are suspected of having an essential role in disease predisposition. This study aimed to know the effect of drought stress and PGPR treatments on disease development. The experiment was arranged in two randomized block designs with two treatments, drought stress, and PGPR. Drought stress treatment consisted of three levels, i.e., W1 = control or without drought stress on 80% field capacity (FC), W2=60% FC, and W3=50% FC, while the PGPR treatment consisted of two levels P1=with PGPR and P2=without PGPR. The results showed that a single treatment of drought stress significantly affected all the indicators of disease development. Meanwhile, its interaction with PGPR treatment only considerably delayed the development of bark canker symptoms. Drought on 60% and 50% field capacity significantly shortened the disease incubation period at 14.4 and 9.7 DAI, increased the disease incidence until 100%, increased area under the disease progress curve (AUDPC) namely 505.8 and 572.2, and reduced plant defense response as indicated by a small number of callus formation namely 0.8 and 0.1callus per plants.